2020
DOI: 10.1002/capr.12314
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of an online pain management programme for patients with ankylosing spondylitis

Abstract: This study was a preliminary attempt to develop and examine an online pain management programme incorporating mindfulness‐informed exercises (i.e. breathing and body scanning exercises) and CBT elements for ankylosing spondylitis patients. Thirty patients diagnosed with ankylosing spondylitis participated in a five‐week online pain management programme, which was delivered primarily through a website. The materials covered by the website included breathing and body scanning exercises, mindful walking exercise,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…All studies were assessed as adequately reported (Multimedia Appendix 10 [16,34,35,47,48,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]), including qualitative studies (8/22, 36%) and mixed methods studies or questionnaire surveys when evaluated both as a whole and with respect to qualitative data on user experience only (14/22, 64%). Overall, each study reported on the study design and questions, participant selection, data collection, and analysis.…”
Section: Critical Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were assessed as adequately reported (Multimedia Appendix 10 [16,34,35,47,48,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]), including qualitative studies (8/22, 36%) and mixed methods studies or questionnaire surveys when evaluated both as a whole and with respect to qualitative data on user experience only (14/22, 64%). Overall, each study reported on the study design and questions, participant selection, data collection, and analysis.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…[...] setting aside time each day for lying down and practising the exercises before sleep and even during the daytime whenever possible, no matter how short the exercise was, could help them build up their perseverance. [Author [68]] However, seeing the value of making mindfulness a habit was not enough to meet the responsibility. Participants reported needing to persist and grapple with the effortful task of making practice a scheduled activity, which involved frequent adjustments to their plans, priorities, and commitments:…”
Section: It Was Difficult In That You Had To Carve Out the Time Reall...mentioning
confidence: 99%
“…The timeframe in which the studies were included ranged from 2009 to 2021. Studies encompassed both digital applications for use on smartphones/ mobile devices [ 21 , 23 25 ] and user-directed online modular programmes [ 9 , 20 , 22 , 26 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of the robustness of the theoretically informed synthesised themes was the final step used in the narrative synthesis. To reduce potential bias, the findings were reanalysed after removing those studies with a medium or low CASP quality rating [ 20 22 ]. This reanalysis confirmed the original synthesised themes and subthemes were robust.…”
Section: Methods and Methodologymentioning
confidence: 99%
“…However, there was a slight increase in the helplessness subscale of the PCS at the 10 week follow-up, suggesting a continued need for psychological support in managing ankylosing spondylitis. Despite these psychological benefits, the overall program did not effectively reduce pain intensity [ 71 ].…”
Section: Search Methodologymentioning
confidence: 99%